PENGARUH ANTARA PENGGUNAAN VARIASI METODE MENGAJAR OLEH GURU EKONOMI TERHADAP MINAT BELAJAR PESERTA DIDIK - Septianti, Ririn Dwi; Matsum, Junaidi H.; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis thesis is entitled "The Influence of the Use of Variations in Teaching Methodsby Economics Teachers on Students' Interest in Learning in Class XI SMA Negeri10 Pontianak". The method used is descriptive method. With the results of the studyas follows: 1) The use of variations in teaching methods by economics teachers atSMA Negeri 10 Pontianak can be concluded that the use of variations in teachingmethods by economics teachers at SMA Negeri 10 Pontianak is very good. 2)Based on the results of the distribution of questionnaires and observations made byresearchers, that the learning interest of class XI students at SMA Negeri 10Pontianak is good. 3) The magnitude of the relationship between the use ofvariations in teaching methods by economics teachers and students' interest inlearning at SMA Negeri 10 Pontianak is based on the results of correlationcalculations. The product moment is 0.735 which, when confirmed in the guidelinesfor providing Interpretation, the correlation coefficient according to Sugiono is inthe interval between 0.60-0.799, which means it has a strong level of relationship.Meanwhile, from the t-test, the t-count value is 6.664 while the t-table is 2.68,which means t-count t-table, thus showing a significant correlation.Keyword : The Use of Variations in Teaching Methods, Students' Interests inLearning, Economic Learning